CREDIBILITY AND POLITICAL COMMUNICATION OF MUHAMMAD SINEN, DEPUTY MAYOR OF TIDORE ISLAND FOR 2015-2020 PERIOD - BurhanudiN A. Muhamad; Nani Nurani Muksin (Universitas Muhammadiyah Jakarta, 2019)
This study discussed the selection of mayor and deputy mayor of Tidore Islands for the 2015-2020 period, which was attended by three candidate pairs namel, number one pair of Hamid Muhammad-Abdurahim Saraha (HARISMA), number two pair of Muhammad Hasan Bay-Mohtar Sangadji (MARASAI), and number three, pair of Capt. Ali Ibrahim-Muhammad Sinen (SAFE). The theory used in this study is political communication, and political credibility, objectives regarding attitudes and regional head elections. Using a qualitative approach with the case study method, this study aims to describe the credibility of political figures related to expertise, and trust in the various abilities of the community during the 2015-2020 election of Tidore Islands deputy mayor. The results of the study indicated that the credibility of political figures was related to the expertise and trust of various elements of society during the 2015-2020 election of Tidore Island deputy mayor. In addition to describing how the views on the construction of the attitude of political figures in a political event, this study also confirms the credibility of political figures with achievements or successes in political events. Keywords: Political Communication, Political Credibility, Political Figure